REKAYASA PERALATAN UPGRADING BATUBARA PERINGKAT RENDAH DALAM UPAYA PENINGKATAN NILAI KALOR MENGGUNAKAN OLI SEBAGAI STABILISATOR - Aswan, Arizal (Politeknik Negeri Sriwijaya, 2019)
Indonesia has 34.320 million tons of low rank coal in 2015. Low rank coal has total moisture content (surface moisture and inherent moisture) which is about 40%. Upgraded Brown Coal (UBC) is a method of removing moisture content in heated light oil. In this study, the proportion of coal and kerosene being 1:1 with a proportioon of lubricant is 0.5% by weight of the coal. This study aims to determine the most optimal coal particle size and operating condition in the UBC process. The coal before upgrading process is known contain 32.56% of inherent moisture and has calorific value as much as 5,240 cal/gr. After upgrading process there is a significant increase of calorific value on coal 200 mesh which is 8,073.11 cal/gr, and reduction of inherent moisture become 2.16%. The most optimal increasing of calorific value occurs in coal 200 mesh, but this product has a sticky (wet) physical properties because it takes a long time in the drying process.